1990
DOI: 10.1128/jcm.28.10.2320-2326.1990
|View full text |Cite
|
Sign up to set email alerts
|

Nonvalue of antigen detection immunoassays for diagnosis of candidemia

Abstract: We evaluated the Cand-Tec (Ramco Laboratories Inc., Houston, Tex.) and LA-Candida antigen detection system (Immuno-Mycologics Inc., Norman, Okla.) tests as possible rapid alternatives to blood cultures for the identification of patients with candidemia. Tests were performed on sera from (i) 33 patients with candidemia, (ii) 82 patients with fever and risk factors for invasive candidiasis, and (iii) 13 healthy controls. A total of 21 patients had no evidence of invasive candidiasis, as determined by clinical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
3

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 29 publications
1
18
0
3
Order By: Relevance
“…For Pastorex Candida, the high specificity is in agreement with earlier findings (23). The specificity of Cand-Tec reported in other studies varied considerably (6,8,12,16,25,26,28).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…For Pastorex Candida, the high specificity is in agreement with earlier findings (23). The specificity of Cand-Tec reported in other studies varied considerably (6,8,12,16,25,26,28).…”
Section: Discussionmentioning
confidence: 90%
“…The presence of Candida antigens in serum appears to be a specific indicator of invasive disease (2,9,15,22,24,28,33). However, the low and varying antigen concentrations, which often fall below the detection limits of the available methods (5,26,33), also lead to controversy about the clinical usefulness of antigen detection tests. In this study, we compared the results of culture and of antibody and antigen detection in a group of 19 patients with or without an antibody response.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of Cand-Tec (70%) in patients with candidemia in the present study was similar to that of beta-glucan and mannan assays, but the specificity was much lower than the other assays. The sensitivity and specificity have varied among reports (6,7,15,16,20), and Phillips reported that the assay was unreliable in candidemic patients (20). D-Arabinitol is a major metabolic product of C. albicans, C. tropicalis, C. parapsilosis, C. solani, and C. guilliermondi.…”
Section: Discussionmentioning
confidence: 99%
“…Im Verlauf einer schweren hämorrhagisch nekrotisierenden Pankreatitis werden Systemmykosen beschrieben. 28 30 Die antimykotische Behandlung von C. albicans (C. tropicalis, C. parapsilosis) sollte initial mit Fluconazol 800 mg die )1 gefolgt von 400 mg die )1 erfolgen. Bei Differenzierung von C. krusei, C. glabrata oder weiteren non-albicans Stämmen sowie resistenten C. albicans sollte die Fluconzoldosis auf 800 mg die )1 (C. glabrata) gesteigert werden bzw.…”
Section: Systemmykosen Bei Hä Morrhagisch Nekrotisierender Pankreatitisunclassified